Efektifitas latihan nebraska agility drill dan shuttle run untuk meningkatkan kelincahan dribble dalam permainan sepakbola pada Ssb Putra Rayung Kususma - Dwicky Nurma Hendra Data (Journal of Physical Activity and Sports (JPAS), 2021)
Footballers at SSB Putra Rayung Kusuma tend to make mistakes when dribbling the ball that is not maximal in training and mini-game conditions, the athlete is not placed in the right position, he should be placed with the athlete's ability, because the coach only obeys the athlete's wishes for positioning. Therefore, the researcher intends to analyze the Nebraska Agility Drill and shuttle run on SSB footballer Putra Rayung Kusuma to find out the footballer's talent. The research method used by the author is experimental. The characteristic in this design is the presence of a control group. The type of data used in this study is premier data. The premiere data in this study were obtained directly from observations at SSB Putra Rayung Kusuma. Based on the results of the t-test, it shows that there is no difference between the two training methods, with t count 0.49> t table 1.73 with a significance value p of 0.67> 0.05, this result shows that there is no difference between the post-test group A and group B. Based on the results of the analysis shows that the increase in the percentage of group A is better than group B, and the average post-test for group A is 17.00 and group B is 17.20 with an average difference of 0.20. Thus the hypothesis which reads "The Nebraska Agility Drill training method is more effective for increasing dribble agility in soccer for athletes aged 12-14 years than shuttle run training", Thus, it can be concluded that the Nebraska Agility Drill Method is more effective for increasing dribble agility in football for athletes aged 12-14 years than shuttle run training with an average difference of 0.20.